(untitled) (Docentes 2.0 Journal, 2015)
This magazine aims to support students, so that they develop their own method of study and thus exploit their full potential, obtaining good academic results and successfully pursuing their career. Safe study requires going beyond reading; It is necessary for the apprentice to process or work in depth the contents of the material to be studied, so it is necessary to learn different and varied techniques, to gradually find which ones are more useful for each type of content.